Transcriptome dynamics of human pluripotent stem cell-derived contracting cardiomyocytes using an embryoid body model with fetal bovine serum. Issue 8 (3rd July 2017) - Jung, Kwang Bo; Son, Ye Seul; Lee, Hana; Jung, Cho-Rok; Kim, Janghwan; Son, Mi-Young
Abstract : Current cardiomyocyte (CM) differentiation protocols did not promote the sufficient expression of genes involved in oxidative phosphorylation for generating adult-like mature CMs. Abstract : Cardiomyocyte (CM) differentiation techniques for generating adult-like mature CMs remain imperfect, and the plausible underlying mechanisms remain unclear; however, there are a number of current protocols available. Here, to explore the mechanisms controlling cardiac differentiation, we analyzed the genome-wide transcription dynamics occurring during the differentiation of human pluripotent stem cells (hPSCs) into CMs using embryoid body (EB) formation. We optimized and updated the protocol to efficiently generate contracting CMs from hPSCs by adding fetal bovine serum (FBS) as a medium supplement, which could have a significant impact on the efficiency of cardiac differentiation. To identify genes, biological processes, and pathways involved in the cardiac differentiation of hPSCs, integrative and comparative analyses of the transcriptome profiles of differentiated CMs from hPSCs and of control CMs of the adult human heart (CM-AHH) were performed using gene ontology, functional annotation clustering, and pathway analyses. Several genes commonly regulated in the differentiated CMs and CM-AHH were enriched in pathways related to cell cycle and nucleotide metabolism. Strikingly, we found that current differentiation protocols did not promote sufficient expression of genes involved in oxidative phosphorylation to differentiate CMs from hPSCs compared to the expression levels in CM-AHH. Therefore, to obtain mature CMs similar to CM-AHH, these deficient pathways in CM differentiation, such as energy-related pathways, must be augmented prior to use for in vitro and in vivo applications. This approach opens up new avenues for facilitating the utilization of hPSC-derived CMs in biomedical research, drug evaluation, and clinical applications for patients with cardiac failure.